1999
DOI: 10.1063/1.479217
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociating trimethylamine at 193 nm to probe dynamics at a conical intersection and to calibrate detection efficiency of radical products

Abstract: This paper reports crossed laser-molecular beam scattering experiments measuring the photofragment velocities and product branching in the photodissociation of trimethylamine (N͑CH 3 ͒ 3 ) at 193 nm. We have observed two primary N-CH 3 bond fission channels that ultimately produce different nitrogen-containing species, CH 3 ϩN͑CH 3 ͒ 2 (X 2 B 1 ); CH 3 ϩN͑CH 3 ͒ 2 *˜CH 3 ϩCH 2 NCH 3 ϩH. The data also indicate that a third minor channel may contribute to the dissociation dynamics, CH 3 ϩN͑CH 3 ͒ 2 †˜C H 3 ϩNC 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…As in other sp 3 nitrogen containing systems such as ammonia, 16 methylamine, 17-20 a selection of secondary and tertiary substituted amines, 21,22 morpholine, 3 and aniline, 23 removal of an electron from the n orbital ͑nmixed HOMO in aniline͒ facilitates an sp 2 ← sp 3 ͑planar← pyramidal͒ change in hybridization at the N center. The first excited singlet state ͑S 1 ͒ is formed by LUMO← HOMO excitation, resulting in a 1 n ‫ء‬ state that is dissociative with respect to extension of the N-H bond length ͑R N-H ͒.…”
Section: Resultsmentioning
confidence: 99%
“…As in other sp 3 nitrogen containing systems such as ammonia, 16 methylamine, 17-20 a selection of secondary and tertiary substituted amines, 21,22 morpholine, 3 and aniline, 23 removal of an electron from the n orbital ͑nmixed HOMO in aniline͒ facilitates an sp 2 ← sp 3 ͑planar← pyramidal͒ change in hybridization at the N center. The first excited singlet state ͑S 1 ͒ is formed by LUMO← HOMO excitation, resulting in a 1 n ‫ء‬ state that is dissociative with respect to extension of the N-H bond length ͑R N-H ͒.…”
Section: Resultsmentioning
confidence: 99%
“…The subsequent dynamics includes the relaxation to the ground state, and the subsequent fragmentation of the hot trimethylamine molecule. Following initial work by Kawasaki et al,44 those processes have been thoroughly investigated in a series of recent papers by Butler, Suits, and collaborators 14,15. Those studies assume that the 3s state is quickly reached regardless of excitation wavelength.…”
Section: Discussionmentioning
confidence: 99%
“…Among the amines, the tertiary amines have the lowest ionization energies,12 causing the Rydberg series to start at a relatively low energy, about 4.5 eV. At excitation wavelengths below 220 nm, TMA has a very low fluorescence quantum yield,13 and following excitation at 193 nm it converts to the ground state surface and dissociates a methyl radical to form the N(CH 3 ) 2 product 14,15…”
Section: Introductionmentioning
confidence: 99%
“…[7] Thee lectronic structure and photodissociation dynamics of TMA have previously been explored using photoionization spectroscopy and molecular beam techniques.C ardoza et al found that optical excitation at 207.8 nm initially prepares the 3p z state. [8] Using time-of-flight photoionization with excitation at 193 nm, Forde et al [10,11] found three dissociative channels:adominant (72 AE 9%)channel involving asequential reaction to N-methylmethanimine (NMMA);aminor channel (27 AE 9%)r esulting in dimethylamine (DMA) and methyl radicals ejected with higher kinetic energy;a nd, possibly,at race amount of at hird channel involving as econdary dissociation of DMA resulting in NC 2 H 4 and molecular hydrogen with low kinetic energy.Inthe dominant pathway,the initially excited TMA first dissociates into DMA and CH 3 ,a nd then DMA fragments to form NMMA and hydrogen atoms.Because the experiments by Forde et al only identified the final reaction products,they could not measure the time scales of the kinetic steps nor confirm the electronic or geometrical structures of the DMA transients.T he intermediate reaction steps and the nature of the transient species therefore remain largely unknown. [9] At higher energy,reached by two-photon excitation with 400 nm, aslightly faster 3s internal conversion time constant of 2.0 ps was found.…”
mentioning
confidence: 99%
“…[9] At higher energy,reached by two-photon excitation with 400 nm, aslightly faster 3s internal conversion time constant of 2.0 ps was found. [8] Using time-of-flight photoionization with excitation at 193 nm, Forde et al [10,11] found three dissociative channels:adominant (72 AE 9%)channel involving asequential reaction to N-methylmethanimine (NMMA);aminor channel (27 AE 9%)r esulting in dimethylamine (DMA) and methyl radicals ejected with higher kinetic energy;a nd, possibly,at race amount of at hird channel involving as econdary dissociation of DMA resulting in NC 2 H 4 and molecular hydrogen with low kinetic energy.Inthe dominant pathway,the initially excited TMA first dissociates into DMA and CH 3 ,a nd then DMA fragments to form NMMA and hydrogen atoms.Because the experiments by Forde et al only identified the final reaction products,they could not measure the time scales of the kinetic steps nor confirm the electronic or geometrical structures of the DMA transients.T he intermediate reaction steps and the nature of the transient species therefore remain largely unknown. Thetime-resolved X-ray scattering experiment reported here provides the missing rate constants of the dissociation paths.W ithin the time window of the experiment, up to 1nsa fter the initial excitation, we found no signature of the secondary dissociation of DMA into NMMA and hydrogen atoms,meaning that the DMA transient appears as af inal reaction product.…”
mentioning
confidence: 99%